Servant Leadership and Employee Engagement Among Generation Z: Examining the Mediating Role of Mental Well-Being - Mahendra Fakhri; Anita Silvianita (Advances in Human Resource Management Research, 2026)
Purpose: This study aims to examine the influence of servant leadership on employee engagement among Generation Z employees and to investigate whether mental well-being mediates the relationship between servant leadership and employee engagement. Research Design and Methodology: A quantitative cross-sectional survey was conducted involving 148 Generation Z employees in Jakarta, Indonesia. Respondents were selected using convenience sampling. Data were collected through online questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings and Discussion: The results indicate that servant leadership has a positive and significant effect on employee engagement. However, mental well-being does not significantly mediate the relationship between servant leadership and employee engagement. These findings suggest that Generation Z employees are more responsive to leadership behaviors characterized by support, empowerment, and service orientation than to their psychological well-being in developing workplace engagement. The results further demonstrate that servant leadership directly strengthens employee engagement without relying on improvements in mental well-being. Implications: Organizations should strengthen servant leadership competencies through leadership development initiatives that emphasize empathy, empowerment, and employee support. Although mental well-being was not a significant mediator, organizations should continue promoting employee psychological health to support workforce sustainability. Originality: This study challenges the assumption that mental well-being is a necessary mechanism linking servant leadership and employee engagement among Generation Z employees.